Prevalence of Japanese encephalitis in pigs in Mainland China during 2000–2024: a systemic review and meta-analysis - Liu, Xue-Tong; Jiang, Li-Dong; Lin, Yu-Ting; Zhao, Ran; Wang, Qi; Zhang, Shu-Ying; Ata, Emad Beshir; Liu, Xin; Wang, Yuan; Liu, Zi-Xuan; Xu, Cui; Xiao, Ying; et al. (Frontiers in Veterinary Science, 2025)
BackgroundJapanese encephalitis (JE) is an acute viral disease transmitted mainly by mosquitoes, primarily affecting Southeast Asia, and the Western Pacific. This study aimed to analyze the factors contributing to JE occurrence in pigs across China.MethodsA systematic search was done using six databases for the published epidemiological studies on porcine JE, including the Chinese Web of Knowledge (CNKI), Wan Fang Database, ScienceDirect, Web of Science, VIP Chinese Journal Database, and PubMed.ResultsA meta-analysis of 31 studies from 2000 to 2024 found an overall prevalence of 35.2% (95% CI: 25.1–46.1). The highest prevalence occurred between 2010 and 2015 at 53.4% (95% CI: 44.2–80.6), from 2010 to 2015, increased precipitation and favorable annual temperatures led to the proliferation of mosquitoes, causing Japanese Encephalitis outbreaks among swine. While the lowest was 2.5% (95% CI: 0.2–6.6) in temperate climates. Serum samples showed the highest prevalence 38.1% (95% CI: 27.9–48.9), and ELISA testing had a higher detection rate 38.2% (95% CI: 24.5–52.9). In the farming mode subgroup, the highest prevalence was observed in the large-scale farming mode at 40.9% (95% CI: 26.4–66.3).ConclusionThe study highlights the spread of JE across China and suggests that it may be underrecognized in some areas. Continuous monitoring and improvements in farming practices are essential for controlling the disease.